2012
DOI: 10.1155/2012/618608
|View full text |Cite
|
Sign up to set email alerts
|

Polymerized-Type I Collagen Induces Upregulation of Foxp3-Expressing CD4 Regulatory T Cells and Downregulation of IL-17-Producing CD4+T Cells (Th17) Cells in Collagen-Induced Arthritis

Abstract: Previous studies showed that polymerized-type I collagen (polymerized collagen) exhibits potent immunoregulatory properties. This work evaluated the effect of intramuscular administration of polymerized collagen in early and established collagen-induced arthritis (CIA) in mice and analyzed changes in Th subsets following therapy. Incidence of CIA was of 100% in mice challenged with type II collagen. Clinimorphometric analysis showed a downregulation of inflammation after administration of all treatments (P < 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 34 publications
(34 reference statements)
0
20
0
Order By: Relevance
“…6 Pregnancy maintenance represents maternal tolerance to the fetal allograft, which is accompanied by special decidual NK cells (dNKs) function 7,8 and a Th2 bias at the maternal-fetal interface. 13 However, the effect of collagen on the phenotype and function of dNKs has not yet been demonstrated. 6 Th2 response as an important regulator of ECM remodeling has been proved to activate collagen deposition in tissue regeneration, 11 and the decreased type IV and V collagen expression was found in human decidual tissue of miscarriage during early pregnancy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Pregnancy maintenance represents maternal tolerance to the fetal allograft, which is accompanied by special decidual NK cells (dNKs) function 7,8 and a Th2 bias at the maternal-fetal interface. 13 However, the effect of collagen on the phenotype and function of dNKs has not yet been demonstrated. 6 Th2 response as an important regulator of ECM remodeling has been proved to activate collagen deposition in tissue regeneration, 11 and the decreased type IV and V collagen expression was found in human decidual tissue of miscarriage during early pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…12 The polymerized collagen has also been proved to ameliorate autoimmune arthritis through the regulation of both regulatory T (Treg)/Th17 differentiation and Th1/Th2 balance. 13 However, the effect of collagen on the phenotype and function of dNKs has not yet been demonstrated. It is also unknown whether abnormal expression of collagen and LAIR-1 at the maternalfetal interface would dysregulate the biological action of dNK involving in pregnancy loss.…”
Section: Introductionmentioning
confidence: 99%
“…RA, of unknown etiology and with complex and varied clinical manifestations, can cause serious damage to human health (4). Type II collagen is a protein that is responsible for organization, predominantly existing in the articular cartilage and eye tissue (3,7). It is the protein that is featured predominantly in the composition of the articular cartilage.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified that, in the limb joints of a mouse RA model, the mice have the same T-cell receptor (TCR) Vβ clone type T cells. However, as the development of the disease progresses, the numbers of this type of clone T cell increase gradually, whereas those of other TCR Vβ clone type T cells are gradually reduced: Therefore, this T cell clone type may be associated with the pathological changes of arthritis (1)(2)(3). Collagen-induced arthritis (CIA) is associated with pathogenetic and pathological changes that are similar to those of RA, and so CIA is often used as a model of human RA (4).…”
Section: Introductionmentioning
confidence: 99%
“…Intralesional injection of this biodrug once a week for 3 months into human hypertrophic scars or scleroderma skin lesions was found to diminish inflammatory infiltrates, modulate type I and III collagen turnover, and downregulate production of pro‐inflammatory cytokines 13,14 . PC has also been shown, both in vitro and in a model of collagen‐induced arthritis, to produce a marked reduction in the severity of arthritis, and to induce downregulation of CD4+ IL17A+T cells and upregulation of T‐regulatory cells (Tregs) and CD4+ IFN‐γ+T cells 15,16 . Thus, PC has potential as a novel therapeutic candidate to suppress autoimmune inflammation by regulating T‐cell differentiation and the balance between pathogenic and regulatory T cells.…”
Section: Introductionmentioning
confidence: 99%